Development of Nearpod-Based Learning Videos in Mathematics Subjects for Junior High School Students - Rifqi, Rifqi; Mukmin, Muhammad Islahul; Muna, Faizul; Nurhuda, Abid (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2023)
This research aims to develop Nearpod-based mathematics learning media. The model used in this research is ADDIE (Analyze, Design, Development, Implementation, Evaluation). This development research is motivated by the need for media that can answer learning challenges in the pandemic era. This product test was carried out at MTs Negeri Batu City involving 30 students in one class. The data collection technique used in this research is a questionnaire to determine students' responses to media readability. The data from this research is qualitative and quantitative. Qualitative data was obtained from criticism and suggestions from validators. Quantitative data was obtained from validation scores and readability questionnaires. The material expert validation results were 91.67%, which means it is very valid. Meanwhile, the media expert validation results were 94.73%. The media readability test value was 83.6% for the limited test, 83.6%, and 82.00% for the wide test.